Critical theory and the philosophy of action in interrogating liberalism within the Frankfurt School project - abdelkrim, fadhila (El Omda in Linguistics and Discourse Analysis, 2022)
One of the many aspects that open the question to understand the ideology of Liberalism , is that it had shaped many principles as well as the philosophy that aimed to draw the attention of the individuals , ultimately to give them social rules in which they can hope to advance with in life in addition to how the results of these principles , this idea made the criticism highlight due to how it generated questions , since the two aspects of Liberalism and the individual are not always compatible , and so the Frankfurt School questions these connections , giving that they had founded the theories regarding social criticism , and among these theories the theory of criticism attempts to discover and question the philosophical context for both the practicality and transcendence of criticism for the principles in the daily life .